Management system for IPv6-enabled wireless sensor networks - Oliveira, Luis M.L. (2012)
“Copyright © [2011] IEEE. Reprinted from Internet of Things (iThings/CPSCom), 2011 International Conference on and 4th International Conference on Cyber, Physical and Social Computing. ISBN 978-1-4577-1976-9 This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”